TFEB overexpression alleviates autophagy-lysosomal deficits caused by progranulin insufficiency - Wren O. Nader; Kaylan S. Brown; Nicholas R. Boyle; Azariah K. Kaplelach; Shaimaa M. Abdelaziz; Skylar E. Davis; Qays Aljabi; Ahmad R. Hakim; Amelia G. Davidson; Giacynta A. Vollmer; Leah C. Wright; J. Bailey Echols; et al. (Scientific Reports)
Abstract Progranulin is a pro-protein that is necessary for maintaining lysosomal function. Loss-of-function progranulin (GRN) mutations are a dominant cause of frontotemporal dementia (FTD). Brains of people with FTD due to GRN mutations accumulate lysosomal storage material and exhibit increased expression of lysosomal transcripts, which may be driven by TFEB and related transcription factors. While this may be a compensatory response to lysosomal impairment, overproduction of lysosomal proteins may also contribute to FTD pathogenesis. To investigate how TFEB may contribute to disease in people with GRN mutations, we analyzed the effects of TFEB overexpression in progranulin-insufficient cells and mice. We generated GRN knockout HEK-293 cells (GRN KO cells), which exhibited increased nuclear localization of TFEB and expression of lysosomal transcripts, but impaired autophagy. TFEB overexpression in GRN KO cells further increased lysosomal transcripts and partially normalized autophagy. We next injected an AAV vector expressing mouse Tfeb (AAV-TFEB) into the thalamus of Grn –/– mice, which accumulates lysosomal storage material. AAV-TFEB increased lysosomal transcripts and reduced immunoreactivity for SCMAS, a marker of lysosomal storage material, in Grn –/– thalamus. These data show that TFEB activity alleviates some autophagy-lysosomal deficits caused by progranulin insufficiency, suggesting potential utility of lysosome-based therapies for GRN-associated diseases.